2019
DOI: 10.3390/cancers11101550
|View full text |Cite
|
Sign up to set email alerts
|

Spironolactone, a Classic Potassium-Sparing Diuretic, Reduces Survivin Expression and Chemosensitizes Cancer Cells to Non-DNA-Damaging Anticancer Drugs

Abstract: Spironolactone, a classical diuretic drug, is used to treat tumor-associated complications in cancer patients. Spironolactone was recently reported to exert anti-cancer effects by suppressing DNA damage repair. However, it currently remains unclear whether spironolactone exerts combinational effects with non-DNA-damaging anti-cancer drugs, such as gemcitabine and epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs). Using the cancer cells of lung cancer, pancreatic cancer, and glioblastoma, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 64 publications
(100 reference statements)
0
11
1
Order By: Relevance
“…Bortezomib also increases the sensitivity of GSC's to temozolomide in a dose and time-dependent manner by downregulating the FOXM1/survivin signaling pathway [245]. Diuretic, spironolactone sensitizes CSCs to Gemcitabine and Osimertinib [246]. Rho-assisted protein kinase inhibitors sensitize pancreatic CSCs to Gemcitabine by downregulating survivin [247].…”
Section: Combination Of Small Molecule Inhibitors With Standard Chemomentioning
confidence: 99%
“…Bortezomib also increases the sensitivity of GSC's to temozolomide in a dose and time-dependent manner by downregulating the FOXM1/survivin signaling pathway [245]. Diuretic, spironolactone sensitizes CSCs to Gemcitabine and Osimertinib [246]. Rho-assisted protein kinase inhibitors sensitize pancreatic CSCs to Gemcitabine by downregulating survivin [247].…”
Section: Combination Of Small Molecule Inhibitors With Standard Chemomentioning
confidence: 99%
“…Importantly for OPALS, in 2019, experimental work again indicating the association between EGFR and the MR showed that spironolactone decreases GB cell survival and sensitized glioma cells to the EGFR inhibitor osimertinib [ 110 ].…”
Section: The Opals Medicinesmentioning
confidence: 99%
“…Spironolactone was also shown to inhibit homologous repair of ds-DNA breaks [ 110 , 111 , 112 , 113 ]. The MOA of this is thought to be by spironolactone’s induction of xeroderma pigmentosum group B (XPB) protein degradation.…”
Section: The Opals Medicinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that CCBs reduce the ball formation, viability and proliferation of ovarian cancer stem cells (CSCs), and induce their apoptosis ( Lee et al, 2020 ). Moreover, recent studies have also suggested that the traditional diuretic spironolactone might increase the death and inhibit cell growth of cancer cells treated with gemcitabine and osimertinibe mainly by regulating the expression of the anti-apoptotic protein surviving ( Sanomachi et al, 2019 ).…”
Section: Anti-hypertensive Drugs Affect Cancer Progression Through Mumentioning
confidence: 99%